Effects of nutritional deficit in the creativity of students of primary school - Matalinares, María (2004)
It is a substantive work in which a descriptive method with a comparative causal design was applied. The purpose was to study chronic nutritional deficit in the creativity of children who attend primary school. It was performed with two matched groups of 644 students with and without nutritional deficit, who were evaluated in fluidity, flexibility, originality and organization. The results showed that no differences existed between children with chronic nutritional deficit and the contrast group, except in two cases: fourth and sixth grade students; and only in the indicators of originality and organization. Children suitably nourished obtained means significantly superior to children with chronic nutritional deficit.